Sequential energy and electron transfer in polynuclear complex sensitized TiO2 nanoparticles - Verma, Sandeep; Kar, Prasenjit; Banerjee, Tanmay; Das, Amitava; Ghosh, Hirendra N. (Journal of Physical Chemistry Letters, 2012)
Polynuclear–polypyridyl complexes exhibit a directional energy-transfer property that can improve their photosensitization activity. In the present work, the energy-transfer process is explored in a trinuclear Ru2∧Os1 complex using transient absorption spectroscopy. This study reveals an efficient excitation energy transfer from the terminal (RuII complex) to the core (OsII complex) region in the ultrafast time domain (400 fs–40 ps). The excitation energy funnel is useful in improving the functionalized core activity. This is evidenced in an interfacial electron-transfer study of Ru2∧Os1, Ru2∧Ru1, and Os1 complex sensitized TiO2 nanoparticle (TiO2 NP) systems. The intramolecular energy transfer causes sequential excitation of the core part of the Ru2∧Os1 complex, which leads to multiexponential electron injection into TiO2 NP. Besides this, the electronic coupling between the metal ion centers stabilizes the positive charge within the trinuclear complex, which results in a slow charge recombination reaction. This study shows that polynuclear complexes can be very useful for their panchromatic effects, unidirectional energy- and electron-transfer properties.